Determinants of Neonatal Mortality in Ghana: Analysis of 2017 Maternal Health Survey Data - Adongo, E.A. (University of Ghana, 2019)
Background: Neonatal mortality contributes about 45% of under-5 mortality globally; 35% in Sub-Saharan Africa; and over 50% of under-5 deaths in Ghana. Though there are existing studies on the determinants of neonatal mortality in Sub-Saharan Africa, not much has been done in Ghana to describe how community level, sociodemographic, health system, maternal and newborn factors individually or in unison interact to influence neonatal mortality. Objectives: The main objective of the study is to examine the determinants of neonatal mortality in Ghana. Method: This study is an analysis of secondary data from the 2017 Ghana Maternal Health Survey (GMHS). The data used in the analysis included only responses from women who delivered live babies in the five years preceding the conduct of the 2017 Ghana Maternal Health Survey and the children lived for at least 28 days. A total of 10,624 respondents were included in the study after data cleaning. Descriptive statistical techniques such as frequency and percentage distribution were used to describe important background characteristics of the women included in the study. Pearson‘s Chi-squares (χ2) test was used to assess the association between the outcome (neonatal death) and independent variables. Multivariate logistic regression analysis was done to estimate odds ratios and control for potential confounders. Confidence level was held at 95%, and a p< 0.05 was considered statistically significant. All the data analysis was done using STATA 15. Results: The prevalence of neonatal mortality was 2% representing 20 per 1000 live births. Three factors predicted neonatal mortality: ANC attendance, sex of baby, and baby being put on mother‘s chest immediately after birth. Women with only 1 ANC visit were less likely to experience neonatal mortality as compared to women with no ANC visit prior to delivery (AOR=0.11; CI=0.02-0.56, p=0.01). Baby girls were less likely (COR=0.68; CI=0.48-0.20; p=0.03) to die during the neonatal period as compared to boys and this did not change when potential confounders were controlled for in a multiple logistic regression model (AOR=0.68,CI=0.47-0.98; p=0.04). The odds of a baby dying within the neonatal period when a baby was not put on the mother‘s chest immediately after birth was 2.5 times (COR=2.46; CI=1.66-3.65, p=0.00). Conclusion: Community level and sociodemographic factors were not significant determinants of neonatal mortality in Ghana. Rather, neonatal, and maternal characteristics did. It is education to families to seek timely and adequate antenatal care should be intensified. This should be done as a family-centred approach to encourage support from other relevants others from the family. Also, targeted Social and Behaviour Change Communication activities should be intensified on immediate skin-to-skin to prevent neonatal hypothermia and promote successful breastfeeding as well as issues on sex differentiation to improve on neonatal outcome
MA. Public Health
Keywords: Neonatal Mortality; Ghana; Maternal Health; Sub-Saharan Africa; Ghana Maternal Health Survey (GMHS); Women